Systematic literature review of the implementation levels of teaching and learning physical education and its effects on students’ physical fitness - Juriah Othman; Borhannudin Abdullah; Saidon Amir; Mohd Rozilee Wazir Norjali Wazir (RSIS International, 2025)
This study examines the effects of Physical Education (PE) teaching and learning (T&L) on students' physical fitness. An Ex Post Facto design assessed differences in the National Physical Fitness Standard for Malaysian School Students (SEGAK) test scores based on PE implementation levels, considering gender and age factors. Data were collected in two phases: the first phase involved 27 head teachers of Physical and Health Education assessing PE implementation using the Malaysian Education Quality Standards Questionnaire Wave 2 (SKPMg2) questionnaire, while the second phase involved 630 students from Forms 1 to 3 across three schools with varying implementation levels. Data were analyzed using ANCOVA in SPSS version 27.0. Findings revealed significant differences in SEGAK scores based on PE implementation levels (F = 7.666, p = 0.001). Bonferroni post-hoc analysis confirmed significant differences between high and medium levels (p = 0.000) and high and low levels (p = 0.022), but no significant difference between medium and low levels (p = 0.112). Gender significantly influenced SEGAK scores, whereas age did not (F = 0.012, p = 0.913). The results suggest moderate PE implementation enhances students' physical fitness more effectively.